Comparative literature a very short introduction - Hutchinson, Ben 1976- (A very short introduction, 2018)
Considering literature comparatively can help readers realize how much can be learned by looking beyond the horizon of their own cultures, discovering not only more about other literatures, but also about their own. Ben Hutchinson offers a history of comparative literature, placing it at the heart of literary criticism.